2013
DOI: 10.1371/journal.pone.0061364
|View full text |Cite
|
Sign up to set email alerts
|

Altered Network Timing in the CA3-CA1 Circuit of Hippocampal Slices from Aged Mice

Abstract: Network patterns are believed to provide unique temporal contexts for coordinating neuronal activity within and across different regions of the brain. Some of the characteristics of network patterns modeled in vitro are altered in the CA3 or CA1 subregions of hippocampal slices from aged mice. CA3–CA1 network interactions have not been examined previously. We used slices from aged and adult mice to model spontaneous sharp wave ripples and carbachol-induced gamma oscillations, and compared measures of CA3–CA1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
3
14
0
1
Order By: Relevance
“…The finding of reduced ripples in old animals is in agreement with previous observations showing reduced energy or power of the ripple oscillation in aged mice (Hermann et al, 2009, Kanak et al, 2013. Furthermore, in keeping with previous in vivo observations (Gerrard et al, 2001) we found that the occurrence and the amplitude of SWRs are similar between adult and old animals.…”
Section: Interpretation Of Age-related Changes In Spontaneous Activitysupporting
confidence: 93%
“…The finding of reduced ripples in old animals is in agreement with previous observations showing reduced energy or power of the ripple oscillation in aged mice (Hermann et al, 2009, Kanak et al, 2013. Furthermore, in keeping with previous in vivo observations (Gerrard et al, 2001) we found that the occurrence and the amplitude of SWRs are similar between adult and old animals.…”
Section: Interpretation Of Age-related Changes In Spontaneous Activitysupporting
confidence: 93%
“…Since ageing is associated with loss of presynaptic terminals 8 9 and altered neuronal functionality 31 , we explored the possibility that the montelukast-induced effect on cognitive function was related to these parameters. Indeed, synaptic density (synaptophysin positive area) was significantly reduced in the hippocampus of old rats, but only slightly and not significantly in the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…In rodent studies, severe mitochondrial damages were observed in the CA1 region when compared to the CA3 region in post-ischemic conditions (Radenovic et al, 2011). Thus, neurons in the CA1 region are more susceptible to mitochondrial damage and oxidative stress when compared to the CA3 region (Kanak et al, 2013). Human gene expression studies reveal that genes involved in energy metabolism were downregulated in AD.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…During aging, the CA3 region is hyperactivated, whereas the CA1 region showed a reduced firing rate (Kanak et al, 2013;Simkin et al, 2015;Oh et al, 2016). As we age, overexcitation of excitatory neurons leads to an excessive accumulation of glutamate in the synaptic cleft (Esposito et al, 2013;Assefa et al, 2018), which results in glutamate-induced toxicity.…”
Section: Role Of Agingmentioning
confidence: 99%